Extension of time and acceleration claims - Oon, Dennis Soon Lee (2006)
One of the most common practical problems faced by many contractors in construction contract is the contract administratorâ€™s failure in granting extension of time in a timely manner. When faced with a non-decision, refusal or late decision by the contract administrator, the contractor must pursue his contractual entitlement to additional time vigorously in order to avoid possible imposition of liquidated damages by the employer for late completion. Alternatively, the contractorâ€™s only recourse is to â€œaccelerateâ€? his works and claim for loss and damage suffered in implementing constructive acceleration measures. This research thus seeks to determine the importance of the contract administratorâ€™s duty in granting extension of time prospectively; and to ascertain the prospect of monetary recovery for loss and expense incurred in the event the contractor chooses to accelerate his works in the absence of timely award for extension of time. This research involved extensive literature review on time-related matters in the construction industry, which resulted in familiarity with the issues and achievement of the objectives of the research. The source of materials widely used include reference to relevant case-laws, books, articles, journals, seminar papers and website resources. The research shows that while a retrospective time extension may be valid in most instances, the contract administrator cannot choose to disregard his duty to administer the construction contract fairly. Thus, where it is possible to decide and reasonable to certify a time extension, the contract administrator must do so without undue delay. A claim for loss and damage may lie against the contract administrator or the employer, should the contractor accelerate the progress of his work to make up for a potential time loss for which an extension of time ought to be properly granted.